2015
DOI: 10.4172/2167-0420.1000253
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Failed Induction of Labor and Associated Factors Among Women Delivered in Hawassa Public Health Facilities, Ethiopia, 2015

Abstract: Background: Induction of labor is an increasingly being done obstetric procedure throughout the world. It is carried out in approximately 20% of all pregnancies. It is associated with poorer outcomes when compared with spontaneous labor.Method: Institutional based cross sectional study was made on medical records of 294 women admitted for induction of labor in Hawassa public health facilities from 1st Jan, to 31st Dec, 2014. Systematic sampling technique was used to select samples. Data was collected by struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
45
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 7 publications
19
45
6
Order By: Relevance
“…In this study was found that the induced labor had shown significant association with Bishop Score, heart rate abnormality and change of meconium color. This finding was in accordance with the study of Bekana et al [19] and Fawole et al [17] who recorded significant associations between those variables and induction of labor. This might be that those variables are the most likely variables indicating the condition of laboring mother and their fetus which are important to determine the need of induced labor.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study was found that the induced labor had shown significant association with Bishop Score, heart rate abnormality and change of meconium color. This finding was in accordance with the study of Bekana et al [19] and Fawole et al [17] who recorded significant associations between those variables and induction of labor. This might be that those variables are the most likely variables indicating the condition of laboring mother and their fetus which are important to determine the need of induced labor.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with Hawassa Public health facilities [19]. This could be explained by the presence of membrane rapture strengthen the cascade of uterine contraction and induced labor.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Dr. Rashida found the reasons for cesarean [59] 2016 26.5 Use of analgesia, higher birth weight, older maternal age Laughon et al [60] 2011 Bishop score Teixeira et al [61] 2012 Bishop score Mbele et al [20] 2007 Primigravidity Hurissa et al [62] 2015 Advanced age, primiparity, unfavorable bishop score, premature rupture of membrane, greater for gestation and bad obstetric history Hatfield et al [15] 2007 Bishop score and parity Grobman [63] 2015 Bishop score and parity Crane [64] 2006 Maternal age, weight, height, BMI, gestational age, birth weight and amniotic fluid index Ennen et al [65] 2009 Drug doses and cervical dilatation Pevnzer et al [66] 2009 Drug doses and cervical dilatation Ehrenthal et al [67] 2010 Drug doses and cervical dilatation Glantz [68] 2010 Drug doses and cervical dilatation BMI: Body mass index…”
Section: Tripathy and Babymentioning
confidence: 99%
“…The major predicting factor for a successful vaginal delivery after induction is the cervical factor [20 [37,62,63]. Similarly, Crane reported the predictive factors as maternal age, weight, height, BMI, ethnicity, and socioeconomic status.…”
Section: Tripathy and Babymentioning
confidence: 99%